Obstacles for physical education teachers in public schools: an unsustainable situation - Renata Osborne; Rachel Saraiva Belmont; Rodrigo Portal Peixoto; Ivone Ouverney Santos de Azevedo; Arlindo Fernando Paiva de Carvalho Junior (Motriz: Revista de Educacao Fisica)
Abstract The study aimed to identify difficulties and aspirations of physical education teachers at public schools in Niterói, inspired by UNESCO's quality physical education goal. An action research containing quantitative and qualitative data was conducted. Thirty-five physical education teachers completed a questionnaire and seven teachers were interviewed. The results indicated that the major difficulties faced were low wages, precarious infrastructure and lack of materials. Physical education is devalued, the space allocated is inadequate, and it is treated as mere recreation. Teachers criticized the lack of commitment of some colleagues who work without planning. They also complained about undisciplined students and lack of interest from their families. They aspire to self-improvement, infrastructure improvements, and more support from school and families. Teachers who do not educate and lack of support from school and government are an unsustainable reality. A synergy of efforts should be implemented, based on a systems view.